Use Of Loanwords For Medical Terms In Interview With The Republic Indonesian Deputy Minister Of Health - Elfa Ali Idrus (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
Health communication has a strong relationship with human efforts to maintain their health, both at the individual, group, organizational, and government levels. Government communication can be seen during an interview with the Deputy Minister of Health of the Republic of Indonesia, Professor Dante Saksono Harbuwono, on the topic "The Indonesian Government's Steps to Prevent Citizens from Going for Treatment Abroad." Interview on December 6, 2023, with CNBC Indonesia media. In the interview session, there was a lot of medical terminology used. This research aims to discover the origins of the medical terms used in this interview, their meanings, and how they are absorbed into Indonesian. This type of research is descriptive qualitative. Each word will receive an explanation of how it was absorbed into Indonesian, namely through adoption, adaptation, translation, and creation. A total of 24 medical terms were absorbed into Indonesian. The most origin language is from English and the biggest absorption process is through adaptation. Given that English is the most used foreign medical terminology, future medical students need to focus on improving their English language proficiency to help academics, communication, and scientific pursuits such as research.